1969
DOI: 10.2337/diab.18.11.717
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Starvation on Plasma Pancreatic Glucagon in Normal Man

Abstract: The role of pancreatic glucagon in starvation has been difficult to assess in humans because of the nonspecificity of antisera heretofore available for glucagon radioimmunoassay. The development of a relatively specific antispnim for pacreation glucagon has now made possible valid measurements of pancreatic glueagun in human plasma and the effect of total starvation on plasma glucagon was, therefore, re-examined. Ten healthy male volunteers abstained from food for seventy-two hours or longer. During this perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
61
0
1

Year Published

1974
1974
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(68 citation statements)
references
References 5 publications
6
61
0
1
Order By: Relevance
“…Indeed, the poorest plasma I R I responses to arginine were observed in the groups (i.e., anorexia nervosa, panhypopituitarism, and isolated growth hormone deficiency) which has blood glucose concentrations (fasting and postarginine infusion) lower than normal; however, the individual differences do not appear to be explained on this basis. Hypoinsulinemia has also been reported in chronic starvation (I I, 17, 23) and prolonged fasting has been reported to blunt the insulin secretory response to arginine (2). Similarly, in the present study, the mean plasma IRI response to arginine in the six adolescent females with anorexia nervosa was significantly less than in the normal group.…”
Section: Plasma Immunoreactive Insulin (Iri) (supporting
confidence: 52%
“…Indeed, the poorest plasma I R I responses to arginine were observed in the groups (i.e., anorexia nervosa, panhypopituitarism, and isolated growth hormone deficiency) which has blood glucose concentrations (fasting and postarginine infusion) lower than normal; however, the individual differences do not appear to be explained on this basis. Hypoinsulinemia has also been reported in chronic starvation (I I, 17, 23) and prolonged fasting has been reported to blunt the insulin secretory response to arginine (2). Similarly, in the present study, the mean plasma IRI response to arginine in the six adolescent females with anorexia nervosa was significantly less than in the normal group.…”
Section: Plasma Immunoreactive Insulin (Iri) (supporting
confidence: 52%
“…35 The observed reduction of plasma glucagon after 24 h fasting is, however, at variance with a previous study in which we observed a 22% increase in plasma glucagon after overnight fasting in mice in conjunction with similar level of glycaemia as in the present study. 42 The glucagon response to fasting is not well understood because both increased, 43 decreased 44,45 and unaffected 46 levels have been reported in humans. Whether these discrepancies in glucagon responses to energy restriction result from different lengths of fasting, different antibodies for the determination of glucagon (some antibodies cross react with immunoglobulins, 47 ) or other conditions, deserves to be studied in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that glucagon en hanced the urinary excretion of sodium and water (12)(13)(14), and when we infused glucagon into the renal artery in non-fasted rats a similar effect was noted (unpublished data). It was also reported that the plasma concentration of glucagon increased early in the fast (14,29,30). These findings suggest that glucagon may play an important role in fasting-induced natriuresis.…”
Section: Discussionmentioning
confidence: 59%